Solid‐State Characterization of 2‐[(2, 6‐Dichlorophenyl)amino]‐Benzaldehyde: An Experimental and Theoretical Investigation. Issue 5 (27th March 2017) - Chen, Peng; Jin, Yuanyuan; Zhou, Panpan; Parkin, Sean; Zhang, Zhifei; Long, Sihui
Abstract : The solid‐state properties of 2‐[(2, 6‐dichlorophenyl)amino]‐benzaldehyde (DCABA) were investigated. Unlike its precursor diclofenac acid, for which three polymorphs are currently known, only one crystalline form of DCABA was found. It was further characterized by other spectroscopic and spectrometric methods including IR, Raman, and UV–vis spectroscopy and powder X‐ray diffraction (PXRD). The thermal behavior of the crystalline form was studied by differential scanning calorimetry (DSC). Theoretical studies, including Hirshfeld surface analysis and conformational energy searches, were performed to provide insight into the factors contributing to the stability of the crystal and to assess the possibility of additional polymorphs. The full characterization of this compound can help fast and accurate identification of DCABA both in dosage forms and in the environment. Abstract : The crystal structure of 2‐[(2, 6‐dichlorophenyl)amino]‐benzaldehyde (DCABA) was determined using single‐crystal X‐ray diffraction. Its spectroscopic and spectrometric properties were investigated by a combination of experimental and theoretical approaches and compared with those of a variety of structurally related compounds. The full characterization of this compound can help fast and accurate identification of DCABA both in dosage forms and in the environment.